Pemetaan Saluran Daerah Irigasi Berbasis Sistem Informasi Geografis (SIG) - Antonio Roberto; Meilani Belladona; Fenty Wisnu Wardhani (MAJALAH TEKNIK SIMES, 2020)
Abstract Seluma Utara Sub district is one of the Sub districts in the Seluma District, where most of the population is working as farmers. This causes the availability of irrigation to be very important to help the community in creating and managing agricultural or plantation land. Along with the rapid development of the area resulting in changes in most of the regional data, especially the form of maps, where the old map has expired (out of date) if compared with statistical data that are currently available. This happens because for the visualization of data in the form of maps requires substantial funds and a relatively long time, so that there are still many areas that still use the old map for planning, implementation and evaluation of development, therefore a mapping of Irrigation Regional (DI) channels is made based. Geographic Information System (GIS) to support the data needs in the District of North Seluma, namely Di Pandan, Talang Empat, and DI Puguk. North Seluma District, Seluma Regency. Data collection for mapping using the Global Positioning System (GPS) is done by tracking or crossing the existing irrigation channels in the field. The results of tracking using GPS are inputted into GPS software and a display of channel information is found in the irrigation area. This map makes it easy for related parties to carry out maintenance and rehabilitation in order to increase agricultural productivity.